2018
DOI: 10.1016/j.ejor.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Investment decisions and sensitivity analysis: NPV-consistency of rates of return

Abstract: Investment decisions may be evaluated via several different metrics/criteria, which are functions of a vector of value drivers. The economic significance and the reliability of a metric depend on its compatibility with the Net Present Value (NPV). Traditionally, a metric is said to be NPV-consistent if it is coherent with NPV in signalling value creation. This paper makes use of Sensitivity Analysis (SA) for measuring coherence between rates of return and NPV. In particular, it introduces a new, stronger defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 78 publications
0
36
0
Order By: Relevance
“…Magni's 37,38 research indicated that the effects of using AIRR and NPV were the same, that is, any decision made by an investor using NPV was the same as a decision made by an investor using AIRR. As NPV is considered to be the most reliable tool in theory, [39][40][41] this study will also use NPV as an indicator to predict the potential economic benefits of carrying out crowdshipping program.…”
Section: Cost Analysismentioning
confidence: 99%
“…Magni's 37,38 research indicated that the effects of using AIRR and NPV were the same, that is, any decision made by an investor using NPV was the same as a decision made by an investor using AIRR. As NPV is considered to be the most reliable tool in theory, [39][40][41] this study will also use NPV as an indicator to predict the potential economic benefits of carrying out crowdshipping program.…”
Section: Cost Analysismentioning
confidence: 99%
“…Woronkowicz (2016) uses data for a sample of non-profit entities and models the relationship between financial vulnerability indicators and facilities investments. The findings of Marchioni and Magni (2018) and Woronkowicz (2016) are evidence of the fact that investments in facilities are associated with the costs of debt associated with facilities projects and influence non-profit finances. Woronkowicz's findings have implications for the financial management of non-profit entities costs of capital (Woronkowicz, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…Long (1976) found that debt to equity decisions must be based on many inputs, including financial valuation, which has not been traditionally applied in the non-profits sector. Reiter et al (2000) claim that decisions about capital structure in non-profits have the same rules as in for-profit entities (Zietlow, 2010;Marchioni & Magni, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While the ROI metric has utility, return is an accounting measure that fails to incorporate both the risk or timing of future payoffs. NPV is based on the discounted cash flow (DCF) model, which is one of the most common models used in the financial world (Brealey et al, 2014;Marchioni and Magni, 2018). Only projects with a positive NPV should be undertaken (Moyer et al, 2017) as they should create shareholder value (Brav et al, 2005).…”
Section: Short-term Perspectivementioning
confidence: 99%